Andrea Verrocchio and His Followers: An Exhibition. Issue 4 (December 2019) - Alt, Gordon
Fifty exceptional works of Andrea del Verrocchio (1435-1488) are on exhibit at the National Gallery of Art in Washington DC. This important exhibit has sculpture, paintings and drawings of one of the most important Renaissance Masters of the fourteenth century. While considered foremost a master sculptor along with Donatello and Michelangelo, he was also noted for his important innovations in painting. As teacher, his workshop was the most important in Florence, and included the young Leonardo da Vinci, Pietro Perugino and Sandro Botticelli. His David and Boy with Dolphin are just of few of the masterpieces included in this important exhibition, which covers a full range of his contributions and will remain on view until January 12, 2020. This is the only opportunity to see this powerful collection in this country as it returns immediately to Italy.